The rise and fall of Scottish common sense realism - McDermid, Douglas (Oxford University Press, 2018)
Reid and the foundations of Scottish common sense – Kames and the argument from perceptual reliability – Reid and the problem of the external world – Stewart and Hamilton : defenders of the faith – Ferrier and the myth of Scottish common sense realism – Ferrier and the foundations of idealism –
9780198789826
Keywords: Stewart; Dugald; Philosophy; Scottish; Realism; Common sense; Ferrier; James Frederick; Hamilton; William; Kames; Henry Home; Reid; Thomas